A Case of Familial Mediterranean Fever with Extensive Lymphadenopathy and Complex Heterozygous Genotype Presenting in the Fourth Decade - Jawad Al-Khafaji; Fran Ganz-Lord; Venkata Rajesh Konjeti; Aaron D. Viny (Case Reports in Rheumatology)
Familial Mediterranean fever (FMF) is an inherited disease caused by loss of function mutations in the MEFV gene encoding pyrin, a negative regulator of interleukin-1. The disease is characterized by recurrent fever and self-limited attacks of joint, chest, and abdominal pain but lymphadenopathy is an infrequent manifestation. While mesenteric lymphadenopathy has been described in several cases in the literature; hilar, paratracheal, axillary, pelvic, and retroperitoneal lymphadenopathy are extremely rare and have been reported separately in very few individuals. In this report, we present a patient with late-onset FMF with extensive lymphadenopathy in all of the aforementioned anatomic regions. Genetic analysis identified three heterozygous pyrin mutations in a patient with no affected family members. Genetic investigation of the patient’s mother identified a novel carrier haplotype E148Q/P369S. The proband also inherited the previously described and rare A744S mutation previously not thought to be a disease-defining lesion. This unique compound heterozygous genotype resulted in a novel genotype-phenotype association producing an atypical clinical presentation of FMF that fits within the pattern of several case reports of late-onset disease with respect to clinical course and therapeutic response.